Genetic Variability, Correlation and Path Coefficient Analysis of Brinjal (SAARC Journal of Agriculture, 2020)
A field experiment was conducted during 2017-2018 for evaluating the performance of brinjal (Solanum melongena L.) genotypes under foothill condition of Nagaland following randomized block design with three replications at the experimental farm of Horticulture, SASRD, Nagaland University, Medziphema, Nagaland. Forty six brinjal genotypes viz. IIVR- 1, IIVR-2, IIVR- 3, IIVR- 4, IIVR-5, IIVR-6, IIVR-7, IIVR-8, IIVR-9, IIVR- 10, IIVR-11, IIVR-12, IIVR-13, IIVR-14, IIVR-15, IIVR-16, IIVR-17, IIVR- 18, IIVR-19, IIVR-20, IIVR-21, IIVR-22, IIVR-23, IIVR- 24, IIVR-25, IIVR- 26, IIVR-27, IIVR-28, IIVR-29, IIVR-30, IIVR-31, IIVR-32, IIVR-33, IIVR- 34, IIVR-35, IIVR-36, IIVR-37, IIVR-38, IIVR-39, IIVR-40, IIVR-41, IIVR- 42, IIVR-43, IIVR-44, IIVR-45 and Nagaland Local (check variety) were evaluated for their growth, yield, quality and genetic attributes. High phenotypic coefficient of variation, genotypic coefficient of variation and high heritability coupled with high genetic advance was found for anthocyanin content, fresh weight of fruit, number of leaves plant-1, yield plant-1, fruit length and fruit diameter. The study on path analysis revealed that maximum positive direct effect on yield is exerted by fresh weight of fruit (1.08) and number of fruits plant-1 (0.407). Based on the experimental results, it can be concluded that, genotype IIVR-31 and IIVR-7 was proved to be potential yielder under foothill condition of Nagaland.SAARC J. Agri., 18(1): 13-21 (2020)